2018
DOI: 10.3390/ijms19051396
|View full text |Cite
|
Sign up to set email alerts
|

CREBH Regulates Systemic Glucose and Lipid Metabolism

Abstract: The cyclic adenosine monophosphate (cAMP)-responsive element-binding protein H (CREBH, encoded by CREB3L3) is a membrane-bound transcriptional factor that primarily localizes in the liver and small intestine. CREBH governs triglyceride metabolism in the liver, which mediates the changes in gene expression governing fatty acid oxidation, ketogenesis, and apolipoproteins related to lipoprotein lipase (LPL) activation. CREBH in the small intestine reduces cholesterol transporter gene Npc1l1 and suppresses cholest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 107 publications
1
39
0
1
Order By: Relevance
“…50 It has been proven that there is a cross-talk between glucose and lipid metabolism. 51,52 In this study, we found that FSH upregulated hepatic cholesterol biosynthesis via promoting AKT-dependent FoxO1 phosphorylation. Our team previously found that FSH enhanced gluconeogenesis without effecting insulin, dependent on AMP-activated protein kinase (AMPK) phosphorylation via GRK2 in the liver.…”
Section: Discussionsupporting
confidence: 49%
“…50 It has been proven that there is a cross-talk between glucose and lipid metabolism. 51,52 In this study, we found that FSH upregulated hepatic cholesterol biosynthesis via promoting AKT-dependent FoxO1 phosphorylation. Our team previously found that FSH enhanced gluconeogenesis without effecting insulin, dependent on AMP-activated protein kinase (AMPK) phosphorylation via GRK2 in the liver.…”
Section: Discussionsupporting
confidence: 49%
“…Studies have shown that the plasma FGF-21 concentration level in the GLP-1Ra intervention group is significantly higher than that in the placebo control group, suggesting that it can participate in regulating liver lipid metabolism by regulating FGF-12 levels. At the same time, studies have shown that cAMP-responsive elementbinding protein H (CREBH) and peroxisome proliferator activated receptor α (PPARα) in the liver mutual coordination plays an important role in regulating lipid metabolism [37,38]. The CREBH-PPARα-FGF21 axis is an indispensable part of the liver involved in mediating lipid and sugar metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…CREBH is primarily expressed in the endoplasmic reticulum (ER) of cells in the liver and small intestine [ 79 , 80 ]. CREBH expression increases in response to fasting through glucagon signaling [ 81 ].…”
Section: Lipid Metabolismmentioning
confidence: 99%